(untitled) (Journal of Health, Population and Nutrition, 2009)
Food-handlers with poor personal hygiene working in food-service establishments could be potential sources of infection due to pathogenic organisms. The study was undertaken to determine the prevalence of bacteria and intestinal parasites among 127 food-handlers working in the cafeterias of the University of Gondar and the Gondar Teachers Training College, Gondar, Ethiopia. Fingernail contents of both the hands and stool specimens were collected from all the 127 food-handlers. The samples were examined for bacteria and intestinal parasites following standard procedures. Coagulase-negative staphylococci were the predominant bacteria species (41.7%) isolated from fingernail contents, followed by Staphylococcus aureus (16.5%), Klebsiella species (5.5%), Escherichia coli (3.1%), Serratia species (1.58%), Citrobacter species (0.8%), and Enterobacter species (0.8%). Shigella species were isolated from stool samples of four food-handlers (3.1%). None of the food-handlers was positive for Salmonella species and Shigella species in res-pect of their fingernail contents. No intestinal parasites were detected from fingernail contents. Intestinal parasites detected in the stools of the food-handlers included Ascaris lumbricoides (18.11%), Strongyloides stercoralis (5.5%), Entamoeba histolytica/dispar (1.6%), Trichuris trichiura (1.6%), hookworm species (0.8%), Gardia lamblia (0.8%), and Schistosoma mansoni (0.8%); 1.6% of the study subjects were positive for each of A. lumbricoides, T. trichiura, hookworm, and G. lamblia. The findings emphasize the importance of food-handlers as potential sources of infections and suggest health institutions for appropriate hygienic and sanitary control measures. Key words: Bacteria; Cross-sectional studies; Diarrhoeal diseases: Food-handlers; Hygiene; Intestinal disÂeases, Parasitic; Parasites; Ethiopia doi:10.3329/jhpn.v26i4.1887 J Health Popul Nutr 2008 Dec:26(4):451-455